Room temperature fabrication of 1D carbon-copper composite nanostructures directly on Cu substrate and their field emission properties - Rosmi, Mohamad Saufi; Yaakob, Yazid; Mohd Yusop, Mohd Zamri; Sharma, Subash; Zulkifli, Zurita; Supee, Aizuddin; Kalita, Golap; Tanemura, Masaki (A I P Publishing, 2016)
This paper demonstrates a carbon-copper (C-Cu) composite nanostructure directly fabricated on a copper (Cu) substrate using the Ar+ ion irradiation method at room temperature. The morphology of C-Cu composite was controlled by a simultaneous carbon supply during ion irradiation. Conical protrusions formed on the surface of the Cu substrate with the low carbon supply rate (RC), whereas high RC area prominently produced nanoneedle structures. The field electron emission (FEE) tests demonstrated significant improvement between conical protrusions and nanoneedle structures, where the emission current increase from 5.70 μAcm−2μAcm−2 to 4.37 mAcm-2, while the turn-on field reduced from 5.90 to 2.00 Vμm−1Vμm−1.